Voices of a contested place: A review of Queer South Rising. Issue 2 (3rd April 2017) - Lavoie, Michelle M.
ABSTRACT: Whitlock's Queer South Rising: Voices of a Contested Place challenges the reader to reconsider their notions of queer and Southern. Whitlock's collection of autobiographical narratives introduces the reader to the complex lives of queer Southerners as they negotiate queer identities at the intersections of race, class, gender, religion, sexuality, and place. Southern queer identity is the antithesis of traditional Southern values, steeped in radical conservatism and fundamentalist Christianity. The editor confronts Southern biases and the myth of homogeneous Southern values by focusing on autobiographies of queer Southerners.